Ghrelin suppresses hypoxia/reoxygenation-induced H9C2 cell pyroptosis via NLRP3: Ghrelin suppresses H/R induced H9C2 pyroptosis - Xu, Li; Su, Jie; Du, Caili; Liu, Hui; Lv, Wei (Cellular and Molecular Biology, 2023)
To study the influence of ghrelin on hypoxia/reoxygenation (H/R) induced H9C2 cell pyroptosis by regulating NLRP3. H9C2 cells were categorized into 3 distinct groups: the control group (referred to as Control), the hypoxia-exposed group (abbreviated as H), and the hypoxia/reoxygenation-exposed group (referred to as H/R). The expression of ghrelin and NLRP3 was determined. Ghrelin overexpression cell line was established to analyze its effects on cell viability, cell cycle and apoptosis. Simultaneously, the assessment of NLRP3 and Caspase-1 expression levels was conducted. To further inspect the effect of ghrelin on H/R treated H9C2 cells via NLRP3, the experimental setups were formulated as follows: control group (Control), H/R group (abbreviated as H/R), Ghrelin overexpression group (Ghrelin), ghrelin overexpression and NLRP3 overexpression group (Ghrelin + NLRP3), NLRP3 overexpression group (NLRP3), NLRP3 negative control group (NLRP3-NC). Experiments mentioned above were performed in each group. In comparison to control, H/R cells expressed significantly lower level of ghrelin, but higher level of NLRP3. Further, a noteworthy reduction in cell viability was evident within the H/R group, with much more cells in G0/G1 phase and less in S phase, and with elevated cell death rate and protein levels of NLRP3 and caspase-1 (P<0.05). Overexpression of ghrelin was capable of increasing cell viability, reducing G0/G1 cell number while increasing S phase cells. Ghrelin overexpression could suppress cell apoptosis and both NLRP3 and caspase-1 expressions. NLRP3 overexpression could diminish the beneficial impacts of ghrelin on H/R treated H9C2 cells. Ghrelin exhibited the capability to suppress H/R induced H9C2 cell pyroptosis through inhibition of NLRP3.